Development of an optical sensor based on surface plasmon resonance phenomenon for diagnosis of dengue virus E-protein - Sheh Omar, Nur Alia (Elsevier, 2018)
Application of surface plasmon resonance (SPR) optical sensor in the diagnosis of dengue virus (DENV) emerged over recent years. Immobilized monoclonal antibody (IgM) on gold/Fe-MPA-NCC-CTAB/EDC-NHS thin film was prepared using a spin coating technique. DENV E-protein can be detected by measuring the SPR signal when IgM immobilized gold/Fe-MPA-NCC-CTAB/EDC-NHS thin film is exposed to the DENV E-protein solution, by varying the concentration ranging from 0.0001 nM to 10 nM. A linear relationship between the shift of SPR angle and concentration of DENV E-protein up to 0.01 nM, with sensitivity of 39.96° nM−1 has been observed. The surface morphology of sensor chip was also recorded using atomic force microscopy to confirm the presence of bound DENV E-protein into IgM surface.